Analyses and optimization of electrolyte concentration on the electrochemical performance of iron-chromium flow battery. (1st August 2020) - Wang, Shaoliang; Xu, Zeyu; Wu, Xiaoliang; Zhao, Huan; Zhao, Jinling; Liu, Jianguo; Yan, Chuanwei; Fan, Xinzhuang
Graphical abstract: Effect of FeCl2, CrCl3 and HCl concentration on the electrochemical performance of iron-chromium flow battery is systematically investigated, and the optimized electrolyte exhibits excellent battery efficiency (energy efficiency: 81.5%) at 120 mA cm −2 . Highlights: Effect of electrolyte concentration of Fe/Cr flow battery is firstly investigated. Electrolyte of 1.0 M FeCl2, 1.0 M CrCl3 and 3.0 M HCl shows the best performance. This work can provide a direct guidance to the application of Fe/Cr flow battery. Abstract: In order to improve the electrochemical performance of iron-chromium flow battery, a series of electrolytes with x M FeCl2  + x M CrCl3  + 3.0 M HCl (x = 0.5, 0.75, 1.0, 1.25) and 1.0 M FeCl2  + 1.0 M CrCl3  + y M HCl (y = 1.0, 2.0, 3.0, 4.0) are prepared, and the effect of electrolyte concentration on the electrochemical performance of iron-chromium flow battery are firstly investigated. The viscosity of electrolyte increases along with the increasing concentration of FeCl2, CrCl3 and HCl, however, the corresponding conductivity decreases with the increasing concentration of FeCl2 and CrCl3 but increases with the increasing HCl concentration. It is worth noting that the electrolyte with 1.0 M FeCl2, 1.0 M CrCl3 and 3.0 M HCl presents the best electrochemical performance due to the synergistic effect of viscosity, conductivity and electrochemical activity. Most importantly, iron-chromium flow battery with the optimized electrolyte presents excellent battery efficiency (coulombic efficiency: 97.4%; energy efficiency: 81.5%) when the operating current density is high up to 120 mA cm −2 . This work can improve the battery performance of iron-chromium flow battery more efficiently, and further provide theoretical guidance and data support to its engineering application.